THE EFFECT OF LEADERSHIP STYLE, COMPENSATION SUITABILITY, INTERNAL CONTROL SYSTEM AND ORGANIZATIONAL CULTURE ON FRAUD IN PT BANK ABCD - Nainggolan, Valentina (Asosiasi Dosen Akuntansi Indonesia, 2020)
This study aims to examine and analyze the effect of leadership style, internal banking control systems, compensation suitability, and organizational culture for fraud at PT Bank ABCD. This research uses causality research with survey method. The population in this study were all credit staff in PT Bank ABCD, amounting to 57 people. Data collection was carried out with a questionnaire delivered directly by the researcher. The sampling method uses the census method in which the entire population in this study is the research sample. The method of analysis uses multiple linear regression analysis. The results showed that (1) leadership style had no significant effect on fraud, and (2) the banking internal control system, compensation suitability and the organizational ethical culture had a negative effect on fraud at PT Bank ABCD.